2016
DOI: 10.19044/esj.2016.v12n4p445
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Approach In Organizational Research: A Review Of Dual-Level Transformational Leadership

Abstract: Due to the nature of organizations as hierarchically nested systems, multilevel theoretical models are relevant to the vast majority of organizational phenomena; hence, the main purpose of this review was clarifying the importance of conceptualization and testing theories at multiple levels of analysis. By doing this, the current study added to the gloom by providing a comprehension literature review with explicit consideration of multilevel directed theory and measures in organizational studies. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…As one of the most important functions of leadership is to motivate people, and lack of motivation may cause process loss and ineffectiveness of teams (Kerr and Bruun, 1983), studies examining the motivational effects of dual-level TFL are needed. However, after reviewing the literature, we find that discussions of the detailed motivational mechanism of dual effects of TFL are quite preliminary (Akinlade, 2014;Pourbarkhordari et al, 2016;Bormann and Diebig, 2020). Wang and Howell (2012) and Tung (2019) demonstrated that group-focused and individualfocused TFL could influence team and individual performance through arousing team member's group identification and leader identification, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…As one of the most important functions of leadership is to motivate people, and lack of motivation may cause process loss and ineffectiveness of teams (Kerr and Bruun, 1983), studies examining the motivational effects of dual-level TFL are needed. However, after reviewing the literature, we find that discussions of the detailed motivational mechanism of dual effects of TFL are quite preliminary (Akinlade, 2014;Pourbarkhordari et al, 2016;Bormann and Diebig, 2020). Wang and Howell (2012) and Tung (2019) demonstrated that group-focused and individualfocused TFL could influence team and individual performance through arousing team member's group identification and leader identification, respectively.…”
Section: Introductionmentioning
confidence: 98%